Comparison of Tool Wear Mechanisms during Drilling of Aluminium Alloy 7075 in Dry and Chilled Air Conditions - Meera Mydin, Nur Munirah; Dahnel, Aishah Najiah; A. Raof, Natasha; Muhamad Khairussaleh, Norkhairusshima; Mokhtar, Suhaily (Journal of Science and Technology, 2022)
Aluminium alloys are widely used in manufacturing industry due to the need of lightweight components and low production cost. However, mechanical assembly of the alloy which requires drilling operations is challenging due to chip accumulation and heat at the cutting tool and workpiece interface. This often causes material adhesion on cutting edges, built-up edge, accelerated tool wear, shorter tool life and poor drilled hole quality. This paper investigates the effect drilling conditions (dry and chilled air at 10°C) on the wear mechanisms of tungsten carbide cutting tools during drilling Aluminium alloy 7075 (Al 7075) at two different feed rates. Chilled or cold air was used as a cooling medium in drilling Al 7075 to promote green manufacturing. Drilling operations of Al 7075 were performed at a constant cutting speed of 123 m/min with feed rates of 0.01 and 0.1 mm/rev. The cutting tools’ flank wear were measured using an optical microscope with Dino-Capture software and further examination on the tool wear (e.g., built-up edge, built-up layer, and crack) were conducted using Scanning Electron Microscopy (SEM). The results of this study indicate that at higher feed rate of 0.1 mm/rev, adhesive wear is dominant due to the presence of evident material adhesion and fractures on the cutting edges. The use of chilled air was found to cause less material adhesion, however more edge fracture occurred which could be due to workpiece hardening. Therefore, it is inferred that drilling Al 7075 with chilled air requires harder and stronger cutting tool in order prolong the tool life.